Influence of Organizational Climate on Employee Job Satisfaction of Nepalese Commercial Banks - Mishra, Archana (Nepalese Journal of Business, 2026)
This study examines on the influence of organizational climate on employee job satisfaction of Nepalese commercial banks. Employee job satisfaction is the dependent variable. The selected independent variables are supervisor support, working environment, incentives, organizational climate and employee relation. The study is based on the primary data with 124 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the influence of organizational climate on employee job satisfaction of Nepalese commercial banks. The study showed that supervisor support has a positive impact on employee job satisfaction. It means that higher the supervisor support, higher will be the employee job satisfaction. Similarly, incentive has a positive impact on employee job satisfaction. It means increase in incentive leads to increase in job satisfaction of employee. Likewise, working environment has a positive impact on employee job satisfaction. It implies that better working environment leads to increase in job satisfaction of employee. Moreover, organizational climate has a positive impact on employee job satisfaction. It indicates that better organizational climate leads to increase in job satisfaction of employee. In addition, employee relation has a positive impact on employee job satisfaction. It means that better employee relation leads to increase in in job satisfaction of employee.